It is currently 20 Nov 2018, 03:42
My Tests

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

If b - c=3, and a+c=32, then a+b=

  Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:
Moderator
Moderator
User avatar
Joined: 18 Apr 2015
Posts: 4916
Followers: 74

Kudos [?]: 980 [0], given: 4506

CAT Tests
If b - c=3, and a+c=32, then a+b= [#permalink] New post 16 Dec 2016, 02:53
Expert's post
00:00

Question Stats:

100% (00:00) correct 0% (00:00) wrong based on 1 sessions
If b - c=3, and a+c=32, then a+b=

(A) 30
(B) 35
(C) 40
(D) 42
(E) 50
[Reveal] Spoiler: OA

_________________

Get the 2 FREE GREPrepclub Tests

Director
Director
Joined: 03 Sep 2017
Posts: 521
Followers: 1

Kudos [?]: 327 [0], given: 66

Re: If b - c=3, and a+c=32, then a+b= [#permalink] New post 29 Sep 2017, 08:26
To get a+b, we can just sum the two expressions side by side so that c eliminates and we are left with \(a+b = 32+3 = 35\).

Answer B
Re: If b - c=3, and a+c=32, then a+b=   [#permalink] 29 Sep 2017, 08:26
Display posts from previous: Sort by

If b - c=3, and a+c=32, then a+b=

  Question banks Downloads My Bookmarks Reviews Important topics  


GRE Prep Club Forum Home| About| Terms and Conditions and Privacy Policy| GRE Prep Club Rules| Contact

Powered by phpBB © phpBB Group

Kindly note that the GRE® test is a registered trademark of the Educational Testing Service®, and this site has neither been reviewed nor endorsed by ETS®.